Temporal structure in the light response of relay cells in the dorsal lateral geniculate nucleus of the cat. - Funke, K (1995)
1. The spike interval pattern during the light responses of 155 on- and 81 off-centre cells of the dorsal lateral geniculate nucleus (LGN) was studied in anaesthetized and paralysed cats by the use of a novel analysis. Temporally localized interval distributions were computed from a 100 ms time window, which was shifted along the time axis in 10 ms steps, resulting in a 90% overlap between two adjacent windows. For each step the interval distribution was computed inside the time window with 1 ms resolution, and plotted as a greyscale-coded pixel line orthogonal to the time axis. For visual stimulation, light or dark spots of different size and contrast were presented with different background illumination levels. 2. Two characteristic interval patterns were observed during the sustained response component of the cells. Mainly on-cells (77%) responded with multimodal interval distributions, resulting in elongated 'bands' in the 2-dimensional time window plots. In similar situations, the interval distributions for most (71%) off-cells were rather wide and featureless. In those cases where interval bands (i.e. multimodal interval distributions) were observed for off-cells (14%), they were always much wider than for the on-cells. This difference between the on- and off-cell population was independent of the background illumination and the contrast of the stimulus. Y on-cells also tended to produce wider interval bands than X on-cells. 3. For most stimulation situations the first interval band was centred around 6-9 ms, which has been called the fundamental interval; higher order bands are multiples thereof. The fundamental interval shifted towards larger sizes with decreasing stimulus contrast. Increasing stimulus size, on the other hand, resulted in a redistribution of the intervals into higher order bands, while at the same time the location of the fundamental interval remained largely unaffected. This was interpreted as an effect of the increasing surround inhibition at the geniculate level, by which individual retinal EPSPs were cancelled. A changing level of adaptation can result in a mixed shift/redistribution effect because of the changing stimulus contrast and changing level of tonic inhibition. 4. The occurrence of interval bands is not directly related to the shape of the autocorrelation function, which can be flat, weakly oscillatory or strongly oscillatory, regardless of the interval band pattern. 5. A simple computer model was devised to account for the observed cell behaviour. The model is highly robust against parameter variations.(ABSTRACT TRUNCATED AT 400 WORDS)